2019
DOI: 10.3390/cells8070745
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and (−)-Epigallocatechin-3-Gallate: Partners in Fighting Cancer

Abstract: We have demonstrated previously that melatonin attenuates hepatotoxicity triggered by high doses of (−)-epigallocatechin-3-gallate (EGCG) in mice. The current work investigated the influence of melatonin on the oncostatic activity of EGCG in two cancer cell lines, wherein melatonin induced an opposite response of p21. In human tongue cancer TCA8113 cells, melatonin-induced p21 and EGCG-mediated formation of quinoproteins were positively associated with the oncostatic effects of melatonin and EGCG. Melatonin-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…These results were validated using an in vivo model of xenograft tumor treated with 25 mg/kg body weight (daily for 18 days) [ 46 ]. More recently, a preliminary study using HepG2 HCC cells, has also confirmed that 3 mM melatonin increased the antiproliferative effects of (–)-epigallocatechin-3-gallate (EGCG) through a p21-associated mechanism [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were validated using an in vivo model of xenograft tumor treated with 25 mg/kg body weight (daily for 18 days) [ 46 ]. More recently, a preliminary study using HepG2 HCC cells, has also confirmed that 3 mM melatonin increased the antiproliferative effects of (–)-epigallocatechin-3-gallate (EGCG) through a p21-associated mechanism [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest on the use of flavonoids as anticancer agents [ 62 ]. In vitro experiments have also demonstrated that 2 and 4 mM melatonin co-administration potentiates the proapoptotic effects of EGCG in HepG2 cells by inhibition of Bcl-2 and COX-2, resulting in an enhanced cytotoxicity against HCC cells [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exploring novel therapeutic drugs is essential for the treatment of ovarian cancer. EGCG has been demonstrated to possess anticancer bioactivity, which has attracted attention; EGCG has demonstrated cancer preventive activity in various types of human cancer, including lung, oral cavity and esophageal cancers (37,38). Numerous studies have been conducted on the effects of EGCG on lung cancer (39)(40)(41)(42), and it had been reported that oral administration of EGCG was feasible and safe to patients with advanced lung cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has shown many beneficial health effects; however, high-dose EGCG is apt to trigger hepatotoxicity [19,20]. We have previously demonstrated that melatonin ameliorated EGCG-induced hepatotoxicity in mice [42] and enhanced anticancer activities of EGCG in vitro [43]. We recently showed that EGCG and DEDTC, both at a safe dose, synergistically induced hepatotoxicity in mice because DEDTC-increased hepatic copper promoted EGCG oxidation [25].…”
Section: Discussionmentioning
confidence: 99%